Quality changes in fresh mango fruits (mangifera indica l. ‘nam dok mai’) under actual distribution temperature profile from Thailand to Japan - Eriko Yasunaga (2018)
Thailand is one of the world’s highest producers of mango, the majority of which are exported to Japan via long supply chains. The mango is a climacteric fruit that ripens after harvest. Therefore, it is very important to treat immature fruits appropriately during lengthy distribution period which can takes approximately three weeks from Thailand to Japan by shipping. The present study aimed to determine the effects of postharvest distribution and storage temperature on physiological changes in fresh mango fruits (Mangifera indica L. ‘Nam Dok Mai’) imported from Thailand to Japan. Immature mango fruits were utilized that were transported immediately after harvest from Thailand by air, and were then stored in the actual distribution temperature conditions of shipping for 3 weeks and also heated to 25°C for 1618 d in the laboratory. Postharvest ripening of immature mango fruits was observed as changes in fruit firmness, peel color, and sugar content under the storage conditions. Softening and coloring were induced during postharvest storage, especially in the first 4 d. After the first 4 d of maturation enhancement, the change in maturation level remained small.